Literature Review: Coal Dust Exposure and Pulmonary Physiology Status - Nadya Safitri Putri (JURNAL KESEHATAN LINGKUNGAN, 2020)
Introduction: Occupational disease is a problem due to the dangers that exist in the work environment. One of the dangers is dust. Dust, either organic or inorganic, is a chemical agent that can cause impairment in the human respiratory tract. As a side result of the processing process in coal mining, coal dust is one example of the danger in the working environment. The flying dust can enter the worker's respiratory tract and cause adverse effects, which should be noted. This study aims to analyze coal dust exposure to pulmonary physiology status and explore what risk factors cause a decline in pulmonary physiology status. Discussion: This study used the literature review method by using research data with the same topic as secondary data. The selected research was a cross-sectional design. The literature review results showed that the inclusion of coal dust was influenced by several variables, such as dust content, age, employment, smoking habits, and the use of PPE. Conclusion: The most widely found variable has a relationship with the pulmonary physiology status is a variable of coal dust levels, age, length of work, and smoking habit.